The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1097/jto.0b013e3181b6be12
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Outcome of Lung Cancer Detection in Patients With and Without Airflow Obstruction in a Primary Care Outpatient Practice

Abstract: A questionnaire, self-administered in a primary care office setting, helps identify patients at high risk of lung cancer. If upcoming results of randomized controlled trials show a benefit of lung screening, this tool could be of help to select patients for screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…BECHTEL et al [114] investigated the efficacy of early detection of lung cancer by chest computed tomography for patients with COPD, and reported that six lung cancer cases were detected among 88 high-risk patients with COPD (6.8%). There were three stage I patients, and three out of six survived for .5 yrs.…”
Section: Importance Of Lung Cancer Screening In Copd Patientsmentioning
confidence: 99%
“…BECHTEL et al [114] investigated the efficacy of early detection of lung cancer by chest computed tomography for patients with COPD, and reported that six lung cancer cases were detected among 88 high-risk patients with COPD (6.8%). There were three stage I patients, and three out of six survived for .5 yrs.…”
Section: Importance Of Lung Cancer Screening In Copd Patientsmentioning
confidence: 99%
“…If upcoming results of randomized controlled trials show a benefit of lung screening, this tool could be of help to select patients for screening. 10 In 13 of the 58 patients in whom it was obtained, HRCT chest detected lesions in the lung; 11 of these 13 patients had lung malignancy. One of the 12 patients with lung cancer in our study had normal HRCT chest; the cancer in this patient was revealed by bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…In the current cohort the prevalence of COPD was 79.6% (95% confidence interval: 75.9%-83.3%). Bechtel et al used a questionnaire to prospectively study over a 5 year period, 430 high risk patients in communitybased primary care, with 126 showing airway obstruction developing lung cancer in 8, but 10 patients without airway obstruction also developed lung cancer [15,16]. Turner and colleagues found an association between self-reported physician-diagnosed chronic bronchitis and emphysema and lung cancer mortality in a prospective study of 448,600 lifelong nonsmokers, yielding 1,759 lung cancer deaths over a 20 year follow up [17].…”
Section: Discussionmentioning
confidence: 99%